IMPLEMENTATION OF BLENDED LEARNING USING ZOOM MEETING - Tissa Maharani (Asosiasi Dosen Muda Indonesia, 2022)
Rapid technology advancements have an impact on education, one of which is blended learning. Blended learning is a combination of physical classroom activities and online technology-assisted learning activities. The goal of this study was to learn more about the utilization of Zoom Meeting application for blended learning, especially in present pandemic. Literary studies are used in the research process. Through Google Scholar, secondary data was gathered from articles, journals, and books, yielding seven journal articles. The conclusion of this study were the Zoom Meeting application may be used in the implementation of blended learning for all levels of education, as well as in training for teachers and lecturers, and the community at the Community Learning Activity Center. This application can increase student learning result; learning process was not monotonous and can grab students' attention; and it has a favorable impact on training students' learning independence. The teacher and community training is also going smoothly and efficiently. The issues include a less stable internet network; its consumes a lot of internet quota; a 45-minute meeting time limit for the first user; educators' and students' lack of understanding of how to use the application; the government's uneven distribution of facilities and infrastructure for delivering free internet, and a lack of training for instructors or lecturers on how to use it in the classroom.